Bacterial meningitis in children with an abnormal craniocerebral structure - Pan, Jiali; Xu, Wei; Song, Wenliang; Zhang, Tao (Frontiers in Pediatrics, 2023)
Background: We studied causative pathogens, clinical characteristics, and outcome of bacterial meningitis with abnormal craniocerebral structure. Methods: A retrospective single-center study was conducted with data for children aged 29 days to 14 years obtained from the PICU in Shengjing Hospital between January 2014 and August 2021. Cases were all children with bacterial meningitis. They were divided into the complex and simple groups according to the presence of abnormal craniocerebral structure before the incidence of bacterial meningitis. We collected data on demographics, clinical presentations, laboratory results, imaging studies, treatments, and outcomes. Results: A total of 207 patients were included (46 in the complex group and 161 in the simple group). The complex patients were lower with mortality (6.5% vs. 11.2%, p < 0.05), positive blood culture (13.0% vs. 34.8%; p < 0.05), multiple organ dysfunction syndrome (0% vs. 9.3%; p < 0.05) and shock (2.2% vs. 9.3%; p = 0.11). The complex patients were more often detected with neurological sequelae (80.4% vs. 53.4%; p < 0.05), cerebrospinal fluid drainage (50% vs. 15.5%; p < 0.05), nosocomial infection (54.3% vs. 3.1%; p < 0.05) and multidrug-resistant bacteria (62.5% vs. 55.6%, p = 0.501). In the complex group, infection was mostly confined to the nervous system. Conclusion: Bacterial meningitis with abnormal craniocerebral structure had fewer bloodstream infection, lower mortality rate, and higher incidence rate of neurological sequelae. Pathogens are more likely nosocomial and multidrug-resistant bacteria